The Educational Thought of Syed Muhammad Naquib al-Attas and Paulo Freire on the Liberation of Education: An Integration of Islamic Spirituality and Critical Consciousness - Miasari; Prasetiya, Benny (Green Publisher, 2026)
Contemporary educational discourse increasingly confronts crises of dehumanization, epistemic domination, and the erosion of ethical orientation within modern schooling systems. In response to these challenges, this article examines the educational philosophies of Syed Muhammad Naquib al-Attas and Paulo Freire as two influential thinkers who, despite emerging from distinct civilizational and epistemological traditions, conceptualize education as a project of liberation. The study aims to explore how al-Attas’s Islamic spiritual epistemology and Freire’s critical pedagogy can be conceptually integrated to formulate a holistic framework for educational liberation. Employing a qualitative research design grounded in library research and thematic content analysis, this study systematically reviews and comparatively analyzes the primary works of both thinkers alongside authoritative secondary sources. The findings reveal that al-Attas emphasizes liberation from epistemological confusion—particularly the loss of adab—through the Islamization of knowledge, whereas Freire foregrounds emancipation from socio-political oppression through the cultivation of critical consciousness (conscientização). Despite these differences, both perspectives converge on the ethical mission of education as a process of humanization, moral responsibility, and transformative praxis. This article contributes theoretically by proposing an integrative paradigm that bridges Islamic spirituality and Western critical pedagogy, challenging the conventional secular–religious dichotomy in educational theory. Practically, it offers an alternative foundation for transformative education that is responsive to global crises of meaning, injustice, and cultural dislocation, thereby advancing a more comprehensive vision of liberatory education.